Compound Salt-Based Coagulants for Tofu Gel Production: Balancing Quality and Protein Digestibility - Zhaolu Li; Sisi Zhang; Zihan Gao; Xinyue Guo; Ruohan Wang; Maoqiang Zheng; Guangliang Xing (Gels, 2025)
Tofu quality is critically influenced by coagulants, though their impact on protein digestibility remains underexplored. This study aimed to investigate the effects of calcium sulfate (CaSO4), magnesium chloride (MgCl2), and their combination (CaSO4 + MgCl2) on the physicochemical properties and protein digestibility of tofu. Water-holding capacity, cooking loss, texture, protein composition, and protein digestibility were analyzed. The results showed that the CaSO4 + MgCl2 combination yielded a water-holding capacity of 99.16%, significantly higher than CaSO4 tofu (93.73%) and MgCl2 tofu (96.82%), while reducing cooking loss to 2.03% and yielding the highest hardness (897.27 g) and gumminess (765.72). Electrophoresis revealed distinct protein retention patterns, with MgCl2 (0.6% w/v) forming denser gels that minimized protein leakage into soy whey. During in vitro digestion, MgCl2-coagulated tofu exhibited superior soluble protein release (5.33 mg/mL after gastric digestion) and higher intestinal peptide (5.89 mg/mL) and total amino acid (123.06 μmol/mL) levels, indicating enhanced digestibility. Conversely, the CaSO4 + MgCl2 combination showed delayed proteolysis in electrophoresis analysis. These findings demonstrate that coagulant selection directly modulates tofu’s texture, water retention, and protein bioavailability, with MgCl2 favoring digestibility and the hybrid coagulant optimizing physical properties. This provides strategic insights for developing nutritionally enhanced tofu products.